The Interaction Between Entrepreneurial Orientation, Strategic Orientation and Tourism marketing: Evidence from Iraqi Tourism Industry - Abbass Kareem, Fadhil; Shakir Abdulhussein Al-Shukri, Bushra; Ahmed Alkaseer, Natalya (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore the relationships between tourism marketing of Iraqi hotels and their entrepreneurial orientation, and strategic orientation as well as to determine the interacted relationship between entrepreneurial orientation, and strategic orientation. To achieve the purposes of the study the quantitative method was used, and three layers questionnaire was organized to reflect the main variables of the study, entrepreneurial orientation, strategic orientation and tourism marketing. The organized questionnaire was applied to 40 hotels (3, 4, and 5 stars hotels) In Iraq by face-to-face interview with the executive managers and the obtained data was analyzed. The findings indicate that entrepreneurial orientation positively affects both of strategic orientation and tourism marketing in our sample. The results also indicate that strategic orientation has an effect on the level of tourism marketing measured by profitability, sales, market share, and overall performance. These results will create an incentive for Iraqi hotel managers to use the entrepreneurial orientation and strategic direction as tools to achieve the objectives of the enterprise, develop behaviors that are consistent with business strategies, and make all employees feel innovative thinking.